Inovasi Terbuka Pada UKM : Kondisi Saat Ini dan Pengembanganya (Tinjauan Bibliometrik Menggunakan VOSviwer) - Rusdi, Wahyudi (Scimadly Publishing, 2022)
The company's open innovation is seen as a result of the availability of complementary resources and transformative capacities that provide critical support. This study aims to systematically analyze the characteristics of the study of open innovation in the scope of SMEs by using data accessed from the Scopus online database by looking at two keywords, namely open innovation and SMEs. This study uses 682 articles and is filtered based on journal requirements between 2008 and 2021 as many as 200 articles. This study answers two critical research questions. First, a bibliometric analysis to answer research questions about how many articles are currently discussing SME Open Innovation Research Trends. This study answers two critical questions in this study. First, bibliometric analysis was used to answer the research question of how many articles currently cover Research Trends in SME Open Innovation. Publications related to open innovation have steadily increased over the past decade. In 2017 and 2021, publications hit a 14-year high. The most cited article is Open Innovation in SMEs: Trends, Motives and Management Challenges by Van de Vrande et al. (2009), with 1,1359 citations. The most influential authors, Van de Vrande et al. (2009), the most influential with 1,359 and followed by Lee et al. (2010) with 886 citations.